Discovering the Components of an Efficient Administrative System with a Focus on the Jihadi Management Approach and Organizational Justice in the Social Security Organization - Rezazadeh, Hamid; Aliahmadi, Alireza; Abdolhamid, Mahdi; Mousavi Loghman, Seyyede Ashraf (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: The objective of this study is to discover the components of an efficient administrative system that also incorporates elements of jihadi management and organizational justice.Methodology: The philosophy of this research is interpretive, the approach is qualitative, the strategy is grounded theory with an emergent approach, and the analysis method is thematic analysis based on Glaserian coding. The study population consists of the managers of the Social Security Organization in Kerman province, which was selected as the statistical population. The sample includes 21 individuals with at least 10 years of relevant work experience and comprehensive knowledge of administrative efficiency processes. Data were collected through semi-structured interviews, and theoretical sampling was employed to select participants. The reliability of the findings (validity and reliability) was ensured using the four criteria proposed by Guba and Lincoln, including credibility, transferability, dependability, and confirmability.Findings: The findings revealed 15 components and 80 categories. These components include administrative efficiency, an efficient culture, organizational justice, corruption control, commitment to jihadi values, high productivity, service quality, transparency and accountability, innovation and continuous improvement, jihadi management, performance management, governance, fair laws, fair behavior, and fair evaluation.Conclusion: The results indicated that these dimensions and components can be considered as the most important criteria for evaluating administrative efficiency and ultimately creating efficiency in the administrative system.